SELECTION OF ALTERNATIVE LOCATIONS FOR MUNICIPAL WASTE LANDFILLS USING GIS AND REMOTE SENSING TECHNOLOGIES - Karimov Farokhiddin,; Tobirov Odiljon, (TADQIQOTLAR, 2025)
Abstract:  Rapid  urbanization  and  population  growth  have  significantly intensified  municipal  solid  waste  management  challenges,  making  the  selection  of suitable landfill sites a critical issue for environmental sustainability and public health. This article examines the application of Geographic Information Systems (GIS) and remote sensing technologies for identifying alternative locations for municipal waste landfills. The study synthesizes existing methodologies and case studies to evaluate environmental,  socioeconomic,  and  infrastructural  criteria  influencing  landfill  site suitability.  Multi-criteria  decision-making  techniques,  including  the  Analytical Hierarchy Process (AHP) and weighted spatial analysis, are emphasized as effective tools for integrating diverse datasets such as land use, topography, proximity to water resources, transportation networks, and population density. The findings highlight that the integration of GIS and remote sensing enhances the accuracy, transparency, and efficiency of landfill site selection, while minimizing potential environmental risks and social  conflicts.  The  article  concludes  that  geospatial-based  approaches  provide  a robust scientific framework for sustainable municipal waste management and support informed  decision-making  aligned  with  long-term  urban  development  and environmental protection goals.